2009
DOI: 10.1152/ajprenal.00049.2008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming of a reduced nephron endowment: more than just a baby's birth weight

Abstract: Moritz KM, Singh RR, Probyn ME, Denton KM. Developmental programming of a reduced nephron endowment: more than just a baby's birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 117 publications
5
90
0
1
Order By: Relevance
“…For example, short-term prenatal glucocorticoid exposure can result in a reduced nephron endowment without changes in kidney weight at birth. 30 Recently, we found no change in kidney weight but an 11% reduction in nephron number in response to ethanol exposure during the latter half of gestation in an ovine model. 9 In the study presented here, we identified a reduction in kidney weight in male ethanol-exposed offspring at PN30 but no reduction in kidney weight in ethanol-exposed female offspring, even although there was a reduction in nephron number.…”
Section: Discussionmentioning
confidence: 83%
“…For example, short-term prenatal glucocorticoid exposure can result in a reduced nephron endowment without changes in kidney weight at birth. 30 Recently, we found no change in kidney weight but an 11% reduction in nephron number in response to ethanol exposure during the latter half of gestation in an ovine model. 9 In the study presented here, we identified a reduction in kidney weight in male ethanol-exposed offspring at PN30 but no reduction in kidney weight in ethanol-exposed female offspring, even although there was a reduction in nephron number.…”
Section: Discussionmentioning
confidence: 83%
“…It might be expected that this was due to comorbidity, but this was not the case. Another possible explanation is that the low nephron mass associated with low birth weight (18) resulted in reduced residual renal function, a recognized risk factor for mortality on dialysis (6); however, the causes of death were varied, and there is no obvious explanation for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another example of permanent alteration induced by developmental plasticity is provided by the observation that adult nephron numbers are reduced both in humans and in animals exposed to suboptimal uterine environment that develop hypertension in adult life. [15][16][17][18] This might represent the consequence of a biological trade-off to spare energy in response to in utero nutrient deprivation, having immediate but no long-term adaptive value.…”
Section: The Mechanisms Of Programmingmentioning
confidence: 99%